ANALISIS KINERJA KEUANGAN KOPERASI SIMPAN PINJAM DAN PEMBIAYAAN SYARIAH BMT ARTHA BAROKAH DI KECAMATAN IMOGIRI - Nur Zakiah; Gendro Wiyono; Risal Rinofah (Jurnal Ilmiah Manajemen Kesatuan, 2022)
The research was conducted to see the development of KSPPS BMT Artha Barokah's financial performance in 2015-2019 by looking at aspects: capital, productive asset quality, efficiency, liquidity, cooperative identity as well as aspects of independence and growth. The research is descriptive quantitative, namely by analyzing financial data and then the results are presented in the form of numbers. The variables studied were the financial performance of KSPPS BMT Artha Barokah with documentation techniques. For data analysis using the instrument of the Regulation of the Deputy for Supervision of the Ministry of Cooperatives and UKM for Health Assessment of Savings and Loans Cooperatives and Sharia Financing Number 07/Per/Dep.6/IV/2016. From the research results, it is known that the financial performance of KSPPS BMT Artha Barokah in 2015-2019 is seen from: 1) The aspect of capital with the ratio of own capital to total assets is not healthy and the CAR is quite healthy; 2) The quality aspect of earning assets in the ratio of non-performing financing to the number of receivables and current financing, the ratio of risky portfolio financing is in the non-risk criteria while the PPAP ratio is doubtful; 3) The aspect of efficiency in the ratio of operational costs to services is less efficient, the ratio of fixed assets to total assets is good while the ratio of service efficiency is not good; 4) The liquidity aspect of the less liquid cash ratio and the less liquid financing to funds received ratio; 5) aspects of cooperative identity in high gross participation ratio and beneficial PEA ratio; 6) Aspects of independence and growth in low asset profitability ratios, low equity profitability ratios and less service operational independence ratios. Based on the results of the study, the financial performance of KSPPS BMT Artha Barokah was in the fairly healthy category although it had experienced a decline in several aspects.